1975
DOI: 10.1126/science.1179221
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Hyperphagia: Dissociation from Hyperphagia Following Destruction of Noradrenergic Neurons

Abstract: impulse (17). Our results cannot be attributed to the experimental procedure itself, since identically treated control animals that received immunoglobulins from nonmyasthenic humans showed none of the myasthenic features. Furthermore, dialysis performed during preparation of the immunoglobulin fraction would remove any residual anticholinesterase medication from the patients' serums.Our study differs from the many previous attempts to transfer myasthenia gravis to animals over the past three decades (6) in at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

1976
1976
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(26 citation statements)
references
References 16 publications
2
24
0
Order By: Relevance
“…1) and these results were consistent with those in rats (Ahlskog and Hoebel, 1973;Ahlskog et al, 1975). However, this effect was temporary a n d food i n t a k e w a s not increased after 6 0 min postinjection (Fig.…”
Section: Resultssupporting
confidence: 93%
“…1) and these results were consistent with those in rats (Ahlskog and Hoebel, 1973;Ahlskog et al, 1975). However, this effect was temporary a n d food i n t a k e w a s not increased after 6 0 min postinjection (Fig.…”
Section: Resultssupporting
confidence: 93%
“…First, we previously reported that PVH DSAP lesions, which also reduced d␤h-ir terminals throughout ARC and medial hypothalamus, produced a significant, but slowly developing obesity during the 6-month post-lesion survival time of the lesioned rats (33), whereas rats with the same lesion killed after 5 wk were not obese (22). Secondly, interruption of the ventral NE and E bundle by midbrain injection of the catecholamine toxin, 6-hydroxydopamine, which also increases NPY gene expression, as well as up-regulating NPY Y5 receptors (48), produces a gradually developing obesity (77)(78)(79). On the other hand, a variety of results demonstrate that NPY neurons are disparate in function and subject to a variety of controls (50, 80 -83).…”
Section: Discussionmentioning
confidence: 98%
“…Our results also suggest that catecholamine neurons couple potent orexigenic neural circuitry within the hypothalamus with hindbrain glucose sensors that monitor brain glucose supply. (Endocrinology 144: [75][76][77][78][79][80][81][82][83] 2003) N EUROPEPTIDE Y (NPY) AND agouti gene-related protein (AGRP) are neuropeptides that have been strongly implicated in the control of appetite. Though neurons producing NPY are widely distributed throughout the central and peripheral nervous system, the highest concentration of NPY cell bodies is in the arcuate nucleus of the hypothalamus (ARC) (1).…”
mentioning
confidence: 99%
“…Taking the finding into consideration that rats with destruction of the medial hypothalamus overeat both in the light and dark cycle, not displaying a diurnal variation (AHLSKOG et al, 1975), whereas normal rats eat more food in the dark cycle, indicating that the medial hypothalamus is acting to inhibit feeding even in the light cycle, it was possible that injected VIP inhibited the neuronal activity in the medial hypothalamus in the light cycle whereas it facilitated it during the dark cycle.…”
Section: Discussionmentioning
confidence: 99%
“…When administered directly in the PV or VM during the light cycle, it induced feeding responses in satiated rats (LEIBOwITz, 1978;MATTHEWS et al, 1978), and when administered in the lateral hypothalamus, it inhibited feeding during the light cycle and facilitated during the dark cycle (MARGULES et al, 1972) in rats. Taking the finding into consideration that destruction of noradrenergic bundles with 6-hydroxydopamine facilitated feeding only in the dark cycle (AHLSKOG et al, 1975), it seems that the noradrenergic transmission exerts, as a whole, an influence on the hypothalamic nuclei to prevent overeating in the dark cycle, whereas it exerts some facilitatory influence in the light cycle. On the VM and PV, the norepinephrine effect is assumed to be inhibitory in the light cycle but facilitatory in the dark cycle.…”
Section: Discussionmentioning
confidence: 99%